Targeting Bile Acid Receptors: Discovery of a Potent and Selective Farnesoid X Receptor Agonist as a New Lead in the Pharmacological Approach to Liver Diseases - Festa, Carmen; De Marino, Simona; Carino, Adriana; Sepe, Valentina; Marchianò, Silvia; Cipriani, Sabrina; Di Leva, Francesco S.; Limongelli, Vittorio; Monti, Maria C.; Capolupo, Angela; Distrutti, Eleonora; Fiorucci, Stefano; et al. (Frontiers in Pharmacology, 2017)
Bile acid receptors represent well-defined targets for the development of novel therapeutic approaches to metabolic and inflammatory diseases. In the present study, we report the generation of novel C-3 modified 6-ethylcholane. The pharmacological characterization and molecular docking studies for the structure-activity rationalization, allowed the identification of 3-azido-6α-ethyl-7α-hydroxy-5β-cholan-24-oic acid (compound 2), a potent and selective FXR agonist with a nanomolar potency in transactivation assay and high efficacy in the recruitment of SRC-1 co-activator peptide in Alfa Screen assay. In vitro, compound 2 was completely inactive towards common off-targets such as the nuclear receptors PPAR, PPAR, LXR, and LXRand the membrane G-coupled bile acid receptor, GPBAR1. This compound when administered in vivo exerts a robust FXR agonistic activity increasing the liver expression of FXR-target genes including SHP, BSEP, OST and FgF21, while represses the expression of genes that are negatively regulated by FXR (CYP7A1), and collectively these effects result in a significant reshaping of bile acid pool in mouse. In summary, compound 2 could represent a promising candidate for drug development in liver metabolic disorders